Avaliação da usabilidade dos portais discente e docente do sistema SIGAA-UFPA na perspectiva dos usuários - SOUZA, Thiago Oliveira de (2019)
The present work aims to evaluate the usability of the student and teacher portals present in the Integrated System of Management of Academic Activities (SIGAA) of the Federal University of Pará (UFPA) from the perspective of the users, in order to verify the efficiency of the accomplishment of the tasks in the system, as well as verify the interaction between the professor and the student. For this, the work had as a descriptive methodology, doing a survey of data through online questionnaires, having a total of 77 participants, corresponding to 64 students and 13 professors. In the questionnaire, objective and subjective questions were asked about functionalities and activities made available to the users related to each portal, in order to evaluate the efficiency of the system in relation to the accomplishment of activities and tasks and user satisfaction in its use. The results of the data analysis indicate that the majority were evaluated positively, presenting good interface and clarity in their messages. In activities assigned as common, in which users are accustomed to perform, realization of enrollment, verification of history and grades, by the student and registration of grades and frequencies, register course plan and content program by the professor, however, in the activities related to interaction with the student, such as participation in chats, downloading and uploading files, the system proved to be ineffective for the majority, especially for students, many not using this functionality and the minority that uses it evaluated negatively, leaving this system function to be desired because it has great potential in the teachinglearning assist.